PENYUSUNAN SISTEM FLOWCHART PENDAFTARAN NASABAH DAN PENERIMAAN SIMPANAN SETORAN (BUMDes) DI DESA POMAHAN KECAMATAN PULUNG KABUPATEN PONOROGO (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
The report, entitled "Preparation of the Customer Registration Flowchart System and Receiving Deposits of Deposits (Bumdes) in Pomahan Village" This is one of the requirements for the Job Training (KKN) task in each work program that has been completed in Pomahan village, Pulung District, Ponorogo Regency, Java East.The preparation of the customer registration flowchart system is very useful for BUMDes for prospective customers who want to register as BUMDes members and for the flowchart system for deposit receipts that I have also arranged is very useful so that customers who want to save money understand and understand the flow in BUMDes, and for us KKN work program and aims to share information about the many benefits of the System Preparation for Bumdes administrators in Pomahan village.In this report, we describe the deposit flow system on BUMDes, which begins with filling in the post test and pre-test of the management, the presentation of material by myself and closes with a group photo. After making a system of customer registration flowchart and deposit deposit receipts (Bumdes), BUMDes administrators know the flow for customer registration and customer acceptance